Saving-Investment Correlations : Immobile Capital. Government Policy or Endogenous Behavior? (IMF Working Papers; Working Paper, 1989)
This paper analyzes reasons for the high post-war correlations of saving and investment, both across countries and over time. It is concluded that the main reason for the observed high correlations over the recent period is probably government policy.